Visibility impact of new commercial development on historical landmarks of world heritage site in Bandar Hilir, Melaka, Malaysia - Ismail, Haris Freddy (2011)
Image and character of a town or city were influenced most by the history of the place. In order to sustain the city’s image and character, preservation on the visibility of landmark is important. However recently, the new commercial development which grows surrounds the historical landmark in Bandar Hilir,Melaka have unquestionably effects the visibility in the area. The purpose of this study is to measure the amount of visibility impact by constructing 3D GIS later to be analysed by using “Viewshed Analysis” (GIS). Outcome from the visibility impacts of new commercial development on historical landmark will be measured and validated by conducting a structured survey and indepth interview. The survey will be focussing on the public awareness on significance of historical landmark while the questionnaire will be concentrated on the professional perspective on issues of the new development within the historical landmark. A proposed recommendation design to improve the visibility of historical landmark is expected to be produced at the end of the research. This recommendation will be useful for the architects, designers and planners as their strategy in developing commercial buildings especially within a sensitive area in the World Heritage Site of Bandar Hilir, Melaka.